Subcortical and default mode network connectivity is impaired in myalgic encephalomyelitis/chronic fatigue syndrome - Inderyas, Maira; Thapaliya, Kiran; Marshall-Gradisnik, Sonya; Barth, Markus; Barnden, Leighton (Frontiers in Neuroscience, 2024)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex chronic condition with core symptoms of fatigue, and cognitive dysfunction suggesting a key role for the central nervous system, in the pathophysiology of this disease. Several studies have reported altered functional connectivity (FC) related to motor and cognitive deficits in ME/CFS patients. In this study, we compared functional connectivity differences between 31 ME/CFS and 15 healthy controls (HC) using 7 Tesla MRI. Functional scans were acquired during a cognitive Stroop color-word task and blood oxygen level-dependent (BOLD) time-series were computed for 27 regions of interest (ROIs) in the cerebellum, brainstem, and salience and default mode networks. Region-based comparison detected reduced FC between the pontine nucleus and cerebellum vermis IX (p=0.027) for ME/CFS patients compared to HC. Our ROI-to-voxel analysis found significant impairment of FC within ponto-cerebellar regions in ME/CFS. Correlation analyses of connectivity with clinical scores in ME/CFS patients detected associations of FC with ‘duration of illness’ and ‘memory scores’ in salience network hubs and cerebellum vermis, and with ‘respiratory rate’ within medulla and the default mode network FC. This novel investigation is the first to report extensive involvement of aberrant ponto-cerebellar connections consistent with ME/CFS symptomatology. This highlights the involvement of the brainstem and the cerebellum in the pathomechanism of ME/CFS.